Association of atrial nicotinamide adenine dinucleotide phosphate oxidase activity with the development of atrial fibrillation after cardiac surgery. - Kim, Y; Kattach, H; Ratnatunga, C; Pillai, R; Channon, K; Casadei, B (2008)
OBJECTIVES: Our goal was to evaluate the role of myocardial nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity and plasma markers of oxidative stress in the pathogenesis of post-operative atrial fibrillation (AF). BACKGROUND: Atrial fibrillation is a common complication of cardiac surgery, leading to increased morbidity and prolonged hospitalization. Experimental evidence suggests that oxidative stress may be involved in the pathogenesis of AF; however, the relevance of this putative mechanism in patients undergoing cardiac surgery is unclear. METHODS: We measured basal and NADPH-stimulated superoxide production in right atrial appendage samples from 170 consecutive patients undergoing conventional coronary artery bypass surgery. Plasma markers of lipid and protein oxidation (thiorbabituric acid-reactive substances, 8-isoprostane, and protein carbonyls) were also measured in blood samples drawn from a central line before surgery and after reperfusion. RESULTS: Patients who developed AF after surgery (42%) were older and had a significantly increased atrial NADPH oxidase activity than patients who remained in sinus rhythm (SR) (in relative light units/s/mug protein: 4.78 +/- 1.44 vs. 3.53 +/- 1.04 in SR patients, p < 0.0001). Plasma markers of lipid and protein oxidation increased significantly after reperfusion; however, neither pre-operative nor post-operative measurements differed between patients who developed AF and those who remained in SR after surgery. Multivariate analysis identified atrial NADPH oxidase activity as the strongest independent predictor of post-operative AF (odds ratio 2.41; 95% confidence interval 1.71 to 3.40, p < 0.0001). CONCLUSIONS: Atrial NADPH oxidase activity is independently associated with an increased risk of post-operative AF, suggesting that this oxidase system may be a key mediator of atrial oxidative stress leading to the development of AF after cardiac surgery.